2022
DOI: 10.37349/etat.2022.00091
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the impact of COVID-19 pandemic on breast cancer at a single Italian institution

Abstract: Aim: To evaluate the local impact of the coronavirus disease 2019 (COVID-19) pandemic on breast cancer (BC) care, with particular attention to the economical and psychological consequences of the possible delay of new diagnoses and treatments. Methods: Three years’ activity (from 2019 to 2021) has been compared. The number of BCs diagnosed from the total amount of mammographic and ultrasound (US) examinations performed in women aged more than 40 years old has been considered. A Pearson’s chi-squared test was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Many studies discussed the changes in staging trends before and after the pandemic. 12,2628 A study conducted in the United Kingdom by Borsky et al reported an increase in node-positive disease on presentation in 2020 compared to 2019 (36.2% vs. 23.6%, p = 0.0063), an increase in metastatic disease at presentation (8.0% vs. 2.9%, p = 0.0295) and increased in median UICC TNM stage at detection from 1b to 2a ( p = 0.0184). Conversely, a Turkish study by Kara et al did not find any statistically significant differences in tumor size, nodal involvement, or overall TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies discussed the changes in staging trends before and after the pandemic. 12,2628 A study conducted in the United Kingdom by Borsky et al reported an increase in node-positive disease on presentation in 2020 compared to 2019 (36.2% vs. 23.6%, p = 0.0063), an increase in metastatic disease at presentation (8.0% vs. 2.9%, p = 0.0295) and increased in median UICC TNM stage at detection from 1b to 2a ( p = 0.0184). Conversely, a Turkish study by Kara et al did not find any statistically significant differences in tumor size, nodal involvement, or overall TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a BC that is not screendetected in women with high-density breasts may present as an interval cancer during the time between routine screenings. Accordingly, a correct evaluation of breast density, in association with the use of DBT, may modify the recall rate and the time interval between rounds, supporting an anticipation of diagnosis, especially during these challenging times when women have already suffered from a delay in diagnosis due to the consequences of the COVID-19 pandemic on BC screening [39].…”
Section: Discussionmentioning
confidence: 99%
“…Signifcant, albeit temporary, declines in cancer-related healthcare service utilization have been reported in China shortly following the onset of the COVID-19 pandemic [6]. A single-institution study from Italy [7] identifed a delay in women undergoing screening breast imaging procedures, with concern for the potential for an increase in cancer diagnoses in the future. Tere is, however, limited information on the experience in the US across a wide range of practice locations, particularly in the community setting where much of US healthcare is delivered.…”
Section: Introductionmentioning
confidence: 99%